2013
DOI: 10.1364/oe.21.022699
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonally polarized dual-wavelength single-longitudinal-mode Tm,Ho:LLF laser

Abstract: We first report a diode-pumped continuous wave orthogonally polarized dual-wavelength single-longitudinal-mode laser with a single c-cut Tm,Ho:LuLiF₄ laser crystal. The simultaneous dual-wavelength single-longitudinal-mode laser near 2 μm is realized by using two uncoated intracavity Fabry-Perot etalons. The output wavelengths are 2064 nm in π-polarization and 2066 nm in σ-polarization respectively, which are orthogonal to each other. At the absorbed pump power of 1 W, the maximum single-longitudinal-mode outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Segura et al reported simultaneous CW laser emissions at 1922 and 1946 nm from the single-doped Tm:KLu(WO 4 ) crystal, and the dual-wavelength Tm:KLu(WO 4 ) laser showed polarization switching in the process of increasing pump power [26,27]. More recently, a diode-pumped orthogonally polarized dual-wavelength single-longitudinal-mode (SLM) c-cut Tm,Ho:LLF laser has been reported by our group [28]. At the absorbed pump power of 1 W, the maximum SLM output powers at 2064 and 2066 nm were 76 and 32 mW, respectively.…”
Section: Introductionmentioning
confidence: 77%
“…Segura et al reported simultaneous CW laser emissions at 1922 and 1946 nm from the single-doped Tm:KLu(WO 4 ) crystal, and the dual-wavelength Tm:KLu(WO 4 ) laser showed polarization switching in the process of increasing pump power [26,27]. More recently, a diode-pumped orthogonally polarized dual-wavelength single-longitudinal-mode (SLM) c-cut Tm,Ho:LLF laser has been reported by our group [28]. At the absorbed pump power of 1 W, the maximum SLM output powers at 2064 and 2066 nm were 76 and 32 mW, respectively.…”
Section: Introductionmentioning
confidence: 77%
“…By using an optical spectrum analyzer, we found that the laser wavelength varied in the range of 1965-2060 nm, however the major wavelength located around 2000 nm. That indicates a tunable laser and dualwavelength laser operations [18] can be realized by using intracavity Fabry-Perot etalon or other optical devices. Sample 2 exhibited lower slope efficiency of 1.4% with the output power of 140 mW under the absorbed pump power of 8.2 W. The major laser wavelength located around 2010 nm.…”
Section: Laser Operationmentioning
confidence: 99%
“…In recent years, orthogonally polarized dual-wavelength lasers have attracted much attention for their versatile applications in terahertz (THz) radiation generation, laser interferometry, precision metrology, and differential absorption lidar. Since 2009, orthogonally polarized dual-wavelength lasers have been successfully demonstrated in various rare-earthdoped laser crystals such as Nd:GdVO 4 [1], Nd:YLF (LiYF 4 ) [2][3][4][5][6][7], Nd:LuVO 4 [8,9], Nd:YAP (Al 5 O 12 Y 3 ) [10], Nd:YAG (Y 3 Al 5 O 12 ) [11,12], Nd:YVO 4 [13,14], Nd:LLF (LuLiF 4 ) [15], Nd:LMB (LaMgB 5 O 10 ) [16], Yb:KGW (KGd(WO 4 ) 2 ) [17], Yb:CGB (Ca 3 Gd 2 (BO 3 ) 4 ) [18], Yb:GMB (GdMgB 5 O 10 ) [19], and Tm,Ho:LLF [20]. * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%